Dasar pancasila sebagai moral negara pancasila sebagai dasar perlindungan hak asasi manusia di Indonesia - syahid, muchammad iqbalgntg (Maliki Interdisciplinary Journal, 2025)
Pancasila, as the moral foundation of the Indonesian state, plays a strategic role in safeguarding human rights (HAM) within the nation. This article explores how Pancasila’s values—particularly the second principle, Just and Civilized Humanity—can be integrated into legal, educational, and cultural systems to serve as an ethical basis for human rights protection. Using a normative juridical approach combined with qualitative analysis of national regulations and philosophical insights from thinkers like Notonagoro and Kaelan, the study finds that Pancasila offers a culturally rooted framework for adapting universal human rights principles to Indonesia’s unique context. Key challenges include the weak internalization of Pancasila’s values and the dominance of liberal human rights paradigms. The article proposes strategies to strengthen Pancasila’s role through character education, legal enforcement, and exemplary leadership, aiming to build a human rights system that is just, dignified, and deeply connected to the nation’s identity. <!–EndFragment –>